Efficacy and toxicity of Ipilimumab-Nivolumab combination therapy in elderly metastatic melanoma patients - Stoff, Ronen; Grynberg, Shirly; Asher, Nethanel; Laks, Shachar; Steinberg, Yael; Schachter, Jacob; Shapira-Frommer, Ronnie; Ben-Betzalel, Guy (Frontiers in Oncology, 2022)
Immunotherapy has revolutionized metastatic Melanoma therapy. The most active regimen is combination therapy of Ipilimumab-Nivolumab (Ipi-Nivo) with response rates (RR) of ~60% and median overall survival (OS) of ~6 years. Immune-related adverse events (irAE) are common (~60% develop grade 3-4), and pose a challenge when treating frail patients. We sought to examine whether Ipi-Nivo therapy is feasible in elderly metastatic melanoma patients. Electronic records of patients treated at the Ella Lemelbaum Institute with Ipi-Nivo between the years 2017-2021 were screened for age. Elderly patients were defined as age 75 and older (group A) and were matched with records of patients age <75 (group B). Records were analyzed for baseline parameters, immunotherapy regimen, RR, toxicity and progression-free survival (PFS). Twenty-six relevant patients age >75 (median 77) were identified and were matched to 34 younger patients (median age 57). No statistically significant differences were noted in terms of baseline parameters except for BRAF mutation status (group A 15%, group B 47%, p=0.008). Response rate in group A was 38% and is consistent with previously published data. Median PFS was the same for both groups (A = 5.5 months, B= 7.5 months, p=NS). Treatment was similarly tolerated: 35% of group A patients completed 4 cycles of therapy compared to 28% for group B (p=NS). Grade 2-4 irAE were the same (A=58%, B=66%, p=NS) and there was no difference in the need for hospitalization for G3-4 events between the groups. (A=63%, B=69%, p=NS). Further division into 4 age groups (>80 vs 75-79 in group A and 65-74 vs <65 in group B) found no difference in terms of response rate or G3-4 toxicity. Ipilimumab-Nivolumab combination therapy in elderly metastatic Melanoma patients seems to be well tolerated and efficient in selected elderly patients based on performance status and comorbidities, just as in younger patients. This regimen seems to be a feasible treatment option for this age group.